2020
DOI: 10.3310/phr08100
|View full text |Cite
|
Sign up to set email alerts
|

Reducing loneliness among migrant and ethnic minority people: a participatory evidence synthesis

Abstract: Background To date, there has been little research into the causes of, and solutions to, loneliness among migrant and ethnic minority people. Objectives The objectives were to synthesise available evidence and produce new insights relating to initiatives that aim to address loneliness among these populations, plus the logic, functioning and effects of such initiatives. Data so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 257 publications
(845 reference statements)
0
11
0
Order By: Relevance
“…The findings of this study highlight the importance to also address migrant mothers' disappointment and unhappiness with their social connections. Tackling their loneliness requires increasing their sense of belonging, fostering meaningful and positive friendships with people who they can identify with, and helping them construct a network that will provide reassurance and a sense of community (36,37,42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this study highlight the importance to also address migrant mothers' disappointment and unhappiness with their social connections. Tackling their loneliness requires increasing their sense of belonging, fostering meaningful and positive friendships with people who they can identify with, and helping them construct a network that will provide reassurance and a sense of community (36,37,42).…”
Section: Discussionmentioning
confidence: 99%
“…Community and religious organizations were also identified as helpful. Research has shown previously that these organizations can help reduce loneliness by connecting migrants to resources or by directly offering assistance and by creating a sense of belonging (42). In Quebec, community organizations are integrated into the provincial healthcare network to facilitate referrals and optimize continuity of care (63) and in Montreal there are many that specifically aim to support newcomers and young families living in poverty (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review study of O’Rourke et al ( 2018 ) presented group activities as one of the most-used intervention strategies to address social connectedness and loneliness. Moreover, a recent report by Salway et al ( 2020 ) points out that shared-identity social support groups (similar people coming together to support each other and engage in meaningful activities) exhibit the strongest beneficial effects for migrants. We can therefore recommend looking for ways to continue organizing these outdoor group activities in a COVID-19-friendly way so that people feel safe and are able to participate.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it would be important to set up practice-oriented research. Although a wide range of interventions have been developed to prevent or reduce loneliness among older persons (De Jong Gierveld and Fokkema 2015 ; Fakoya et al 2020 ), only a few are designed specifically for older migrants (Salway et al 2020 ). Academic interest and understanding on the effectiveness of loneliness interventions for older people—or the lack thereof—is developing (Cattan et al 2005 ; Dickens et al 2011 ; Gardiner et al 2018 ), whereas this is almost entirely absent for older migrants.…”
Section: Facing the Future: Opportunities And Challengesmentioning
confidence: 99%